Layered calcium phenylphosphonate: a hybrid material for a new generation of nanofillers - Kopecká, Kateřina; Beneš, Ludvík; Melánová, Klára; Zima, Vítězslav; Knotek, Petr; Zetková, Kateřina (Beilstein Journal of Nanotechnology, 2018)
The use of nanosheets of layered calcium phenylphosphonate as a filler in a polymeric matrix was investigated. Layered calcium phenylphosphonate (CaPhP), with chemical formula CaC6H5PO3∙2H2O, is a hybrid organic–inorganic material that exhibits a hydrophobic character due to the presence of phenyl groups on the surface of the layers. In this paper, various CaPhP synthesis methods were studied with the aim of obtaining a product most suitable for its subsequent exfoliation. The liquid-based approach was used for the exfoliation. It was found that the most promising technique for the exfoliation of CaPhP in an amount sufficient for incorporation into polymers involved using propan-2-ol with a strong shear force generated in a high-shear disperser. The filler was tested both in its unexfoliated and exfoliated forms for the preparation of polymer composites, for which a low molecular weight epoxy resin based on bisphenol A was used as a polymer matrix. The prepared samples were characterized by powder X-ray diffraction, atomic force microscopy, optical and scanning electron microscopy, and dynamic mechanical analysis. Flammability and gas permeation tests were also performed. The addition of the nanofiller was found to influence the composite properties – the exfoliated particles were found to have a higher impact on the properties of the prepared composites than the unexfoliated particles of the same loading
Keywords: exfoliation; layered phenylphosphonate; nanomaterial; nanofiller; polymer filler